PENGARUH KUALIFIKASI AKADEMIK DAN RELEVANSI KEILMUAN TERHADAP PROFESIONALISME GURU MATA PELAJARAN EKONOMI SMAN DI KECAMATAN MANDAU - Widya Lestari Lestari; Gimin '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to determine the effect of academic qualifications and the relevance of science in the professionalism of teachers of economic subjects SMAN in District Mandau. This research was conducted in the District Mandau UPTD and at SMAN in District Mandau from January to March 2015. The research method used is descriptive quantitative method. Population of 32 teachers and 32 teacher sample. Data collection instruments used were the documentation for the independent variables: academic qualifications (X1) and the relevance of science (X2); questionnaires were processed using Likert scale and scale Gutman for dependent variables: the professionalism of teachers (Y). Data analysis technique used is multiple linear regression statistical techniques. From the results, it can be concluded that: (1) academic qualifications influence on the professionalism of teachers; (2) the relevance of the scientific effect on the professionalism of teachers; (3) the influence of academic qualifications and the relevance of science to professionalism amounted to 38.8 Key words : academic qualifications, scientific relevance, the professionalism of teachers.